1962
DOI: 10.1021/jo01051a004
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of dl-18-Norestrone1

Abstract: The synthesis of dl-18-norestrone (11) from the known dl-18-nor-D-homoestrone methyl ether (IVB) is described. The corresponding methyl ether (VIIIB) was shown to be the racemic form of the methyl ether of the compound obtained by alkaline treatment of 18-hydroxyestrone (I), thus confirming the structure of the latter. In the equilibrium mixture of VIIIp and its 13-is0 epimer, the latter predominates in an approximately 2 to 1 ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Accordingly, the diene 16a was treated with a limited amount of ozone in methylene chloride (19) at -70". Chromatography of the neutral portion of the product over silica gel gave the ketone 19 in about 10% yield.…”
Section: Traduit Par Le Journal]mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the diene 16a was treated with a limited amount of ozone in methylene chloride (19) at -70". Chromatography of the neutral portion of the product over silica gel gave the ketone 19 in about 10% yield.…”
Section: Traduit Par Le Journal]mentioning
confidence: 99%
“…(CHCI,) 3200-2400 (carboxyl OH), 1730 sh (monomeric carboxyl), 1690 cm-' (dimeric carboxyl); n.m.r. r 9.14 and 9.11 (two three-proton doublets, non-equivalent methyls of isopropyl), 8.88 Meth~~l13-0xo-7,17-secoacon-8(15)-en-13-on-18-oate (19) A solution of diene 16a (48 mg) in methylene chloride was cooled to -70' and a saturated solution of ozone in methylene chloride (6 ml (19)) at -70" was added. The blue color of the ozone solution soon disappeared.…”
Section: Rerluction Of Ketoacid I2amentioning
confidence: 99%
“…However, if dehydration to 5 was first performed, cyclization gave appreciable quantities of the natural trans-anti-trans 6. Initially this latter sequence gave a 2:1 mixture of 7:6 [3,5], but later experiments [6] showed that 6 (and its demethylated analog) could be made the only readily isolable product (ca. 10%).…”
mentioning
confidence: 99%